Abnormal vaginal bleeding in women of reproductive age: a descriptive study of initial management in general practice - Ankum Willem M; Vervoort Cléo-Lotte AG; Wieringa-de Waard Margreet; de Vries Corlien JH; Bindels Patrick JE (BMC, 2008)
Abstract Background Abnormal vaginal bleeding (AVB) in women of reproductive age is a common reason for consulting a general practitioner. Nevertheless, how general practitioners (GPs) choose to initially manage AVB is largely unknown, as is the prevalence of underlying pathology of AVB in primary care. Methods To investigate the initial diagnostic procedures and treatment for AVB used in general practice, we performed a descriptive study based on computerised medical records. New consultations for AVB in 2000 and 2001 were selected. Patient characteristics, diagnostic procedures and treatment were analysed. Results In total, 270 new consultations were included. The majority of patients (75%) consulted the GP for AVB only once. GPs performed diagnostic procedures in 54% of all consultations. Overall, additional diagnostic procedures revealed abnormalities in 11% of women. However, the diagnostic procedures implemented by the GPs varied widely per bleeding type and contraceptive use. Anaemia was found in 36% of 45 women tested. Uterine fibroids were found in 41% of 27 women examined by ultrasound. Medication was prescribed in 34% of all consultations. A gynaecological referral was registered in 4% of all contacts. Conclusion Initially, GPs tend to follow a policy of expectant management in women of reproductive age with AVB. However, when additional diagnostic procedures were performed, anaemia and uterine fibroids were found in a considerable number of women.